Achieving cleaner water for UN sustainable development goal 6 with natural processes: Challenges and the future - Crockford, Lucy (Frontiers in Environmental Science, 2022)
UN Sustainable Development Goal 6 aims to achieve clean water for all. Access to clean water is a basic human right but can be costly and challenging. Using natural processes to provide cleaner water for treatment is a cost effective, and often beneficial to other ecosystem services, method. Unfortunately, there are a number of barriers to the implementation of natural processes for cleaner water such as the difficulty of funding these nature-based solutions which is linked to the requirement of accurate valuation. Once funded, partnership with land practitioners is important to ensure that detrimental impacts are not experienced elsewhere and to ensure that these natural processes such as ponds and constructed wetlands are maintained and managed appropriately. The future in the UK and Europe, in general, is optimistic despite the large funding gap for nature-based solutions overall. Green finance, essentially a loan or investment to support environmentally-friendly activities, has been developed to funnel money towards sustainable investments with an environmental focus, and the percentage of world wealth spent on such investments has increased.